Effect of plasticizers on the properties of sugar palm nanocellulose/cinnamon essential oil reinforced starch bionanocomposite films - Omar Syafiq, Razali Mohamad; Mohd Sapuan, Salit; Mohd Zuhri, Mohamed Yusoff; Othman, Siti Hajar; Ahmad Ilyas, Rushdan (De Gruyter, 2022)
This work examines the effects of plasticizer type and concentration on mechanical, physical, and antibacterial characteristics of sugar palm nanocellulose/sugar palm starch (SPS)/cinnamon essential oil bionanocomposite films. In this research, the preparation of SPS films were conducted using glycerol (G), sorbitol (S), and their blend (GS) as plasticizers at ratios of 1.5, 3.0, and 4.5 wt%. The bionanocomposite films were developed by the solution casting method. Plasticizer Plasticizers were added to the SPS film-forming solutions to help overcome the fragile and brittle nature of the unplasticized SPS films. Increasing plasticizer contents resulted in an increase in film thickness and moisture contents. On the contrary, the increase in plasticizer concentrations resulted in the decrease of the densities of the plasticized films. The increase in the plasticizer content from 1.5 to 4.5% revealed less influence towards the moisture content of S-plasticised films. For glycerol and glycerol-sorbitol plasticized (G and GS) films, higher moisture content was observed compared to S-plasticised films. Various plasticizer types did not significantly modify the antibacterial activity of bionanocomposite films. The findings of this study showed significant improvement in the properties of bionanocomposite films with different types and concentrations of plasticizers and their potential for food packaging applications was enhanced.